2021
DOI: 10.13057/biodiv/d220447
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of Phaius spp. orchids from Indonesia

Abstract: Abstract. Hartati S, Samanhudi, Manurung IR, Cahyono O. 2021. Morphological characteristics of Phaius spp. orchids from Indonesia. Biodiversitas 22: 1991-1995. Orchid is one of the ornamental plants with great economic value in various communities. Characterization and grouping of several orchid species can be used in breeding efforts to obtain hybrid with the desired traits. This study is aimed to characterize the morphological appearance of Phaius orchids and to cluster the species based on their similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The information can be a reference for crossbreeding to obtain new varieties. A study based on qualitative studies on Phaius orchids showed 0.80 morphological similarities, namely P. amboinensis, P. tankervilae, and P. montanus (Hartati et al 2021a). Based on quantitative characterization, Hartati et al (2021b) reported that P. indigoferus and P. amboinensis performed 0.87 morphological similarities.…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The information can be a reference for crossbreeding to obtain new varieties. A study based on qualitative studies on Phaius orchids showed 0.80 morphological similarities, namely P. amboinensis, P. tankervilae, and P. montanus (Hartati et al 2021a). Based on quantitative characterization, Hartati et al (2021b) reported that P. indigoferus and P. amboinensis performed 0.87 morphological similarities.…”
Section: Cluster Analysismentioning
confidence: 99%
“…Unfortunately, only several species of Dendrobium native to Indonesia have been characterized, such as Indraloka et al ( 2019) have characterized 10 species of Dendrobium and Aprilianti et al (2021) researched Dendrobium seed morphology. Some researchers have studied the morphological characterization of other orchids genera, such as Phalaenopsis (Fauziah et al 2014;Pangestu et al 2014), Vanda (De et al 2015b), Dendrobium (Hidayati et al 2016), and Phaius (Hartati et al 2021a). Therefore, this research aims to characterize the morphology of five species of Dendrobium native to Indonesia in order to assess the potential parental candidates for crosses.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient similarity of (2) Phaius montanus and (3) Phaius collasus are 0.48. This is evident from Hartati's research (2020) that morphologically the Phaius amboinensis orchid and the orchid Phaius tankerville have a similarity of 80% and are divided into 2 clusters [28]. The more similar the morphology of the orchid, the higher the possibility of genetic similarity.…”
Section: B Cluster Analysis Of Phaius Sppmentioning
confidence: 96%
“…Knowledge of plant morphology also has an important role as the basis for determining breeding program strategies, as stated by Rêgo et al (2020) on the ornamental foliage plant of the genus Sansevieria. In its application to ornamental plants, Hartati et al (2021), based on the characterization of five species of Phaius orchids, noted that morphology was important in selecting suitable parents for experimental crosses to obtain hybrids with desirable traits.…”
Section: Introductionmentioning
confidence: 99%